1970
DOI: 10.3329/uhj.v6i2.7245
|View full text |Cite
|
Sign up to set email alerts
|

Study of Coronary Collaterals in Patients with Stable Angina

Abstract: Background: Coronary collateral circulation is an alternative source of blood supply to the myocardium in coronary atherosclerotic disease. They provide adequate flow to the major epicardial branches of the coronary artery. Indicator of cardiac ischemia like stable angina pectoris may determine the presence of coronary collateral circulation.Methods and results: In this prospective observational cross sectional study, 150 patients with stable angina pectoris with or without MI (myocardial infarction) and or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hansen et al and Arzu et al reported patients with collaterals were associated with a higher incidence of chronic stable angina and history of previous myocardial infarction [43][44][45]. Piek et al showed the duration of angina, coronary artery severity, and proximal lesion location were positively associated with coronary collaterals [46].…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al and Arzu et al reported patients with collaterals were associated with a higher incidence of chronic stable angina and history of previous myocardial infarction [43][44][45]. Piek et al showed the duration of angina, coronary artery severity, and proximal lesion location were positively associated with coronary collaterals [46].…”
Section: Discussionmentioning
confidence: 99%
“…9 There were poor development of coronary collateral vessels in patients with metabolic syndrome and incidence of development of coronary collaterals was significantly higher in patients with stable angina pectoris. 10,11 Coronary collaterals appear to play important role in coronary artery disease morbidity and mortality. But the conflicting results remain, and the exact mechanism of collateral formation is still unknown.…”
mentioning
confidence: 99%